2021
DOI: 10.2147/cmar.s287974
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CDH1, FN1 and VIM for Early Recurrence in Patients with Colorectal Liver Metastasis After Liver Resection

Abstract: Purpose: There are limited data on expression of epithelial-mesenchymal transition (EMT) markers in patients with colorectal liver metastases (CRLM). The study aim was to evaluate the expression and prognostic significance of E-cadherin (CDH1), fibronectin (FN1) and vimentin (VIM) in patients with CRLM after curative-intent liver resection. Patients and Methods: Thirty patients with CRLM managed by curative-intent liver resection were included in this prospective pilot study. Blood samples, colorectal liver me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In this study and a previous report by our group [ 10 ], plasma FN level is significantly decreased in CRC patients with the metastatic stage-dependent manner. Consistent with this finding, Bogdanovic et al showed that FN level was down-regulated in tissues and absent in the plasma of patients with CRC liver metastases [ 25 ]. Moreover, Zhou et al, reported that the serum FN level was decreased in patients with metastatic non-small cell lung cancer in comparison to those with non-metastatic lung cancer patients [ 26 ].…”
Section: Discussionsupporting
confidence: 53%
“…In this study and a previous report by our group [ 10 ], plasma FN level is significantly decreased in CRC patients with the metastatic stage-dependent manner. Consistent with this finding, Bogdanovic et al showed that FN level was down-regulated in tissues and absent in the plasma of patients with CRC liver metastases [ 25 ]. Moreover, Zhou et al, reported that the serum FN level was decreased in patients with metastatic non-small cell lung cancer in comparison to those with non-metastatic lung cancer patients [ 26 ].…”
Section: Discussionsupporting
confidence: 53%
“…Reductions in the expression of adhesion molecules in neurons, such as PPM1H, NTSR2, CLDN10, and CDH13, are related to synaptic N‐methyl‐D‐aspartate (NMDA) receptor‐induced long‐term potentiation 69 and affect serotonin (5‐HT) formation, which is potentially relevant to migraine 70,71 . In addition, previous studies have shown that changes in the levels of CNTN1, CDH1, and other cell adhesion proteins in peripheral blood are associated with deficit schizophrenia, which may also be related to hypoxia 72,73 . We also found an increase in CAMs in blood after PFO closure; however, the clinical implications of this change remain to be explored in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…in the formation of a mutated, dysfunctional protein, which further results in decreased cell adhesion and uncontrolled growth of malignant cells [18]. Many studies have shown an association between reduced /absent E cadherin expression and progression of tumors [3,6].…”
Section: The Expression Of E-cadherin On Epithelial Cell Membranes Maintains Cell Connections and Suppresses Cell Invasion Mutation Of Thmentioning
confidence: 99%